Survival Outcomes in Epithelial Ovarian Cancer: The Role of the Ovarian Cancer-specific Comorbidity Index - İrem Küçükşahin; Pınar Karaçin (Acta Haematologica Oncologica Turcica)
Aim: Epithelial ovarian cancer (EOC) is a gynecologic malignancy that is often diagnosed at an advanced stage and is associated with a high mortality rate. Comorbidities may significantly influence treatment planning and survival outcomes in these patients. This study aimed to evaluate the impact of comorbidity on survival in EOC patients using the Ovarian Cancer-Specific Comorbidity Index (OCCI). Methods: This retrospective study included patients with newly diagnosed EOC. Demographic and clinical data, comorbidities, and treatment strategies were recorded. Patients were classified into low-, moderate-, and high-risk groups based on the OCCI, and the associations between progression-free survival (PFS) and overall survival (OS) were analyzed. Results: Significant differences in survival were found among the risk groups. Taking the low-risk group as a reference, hazard raios (HRs) for PFS were 2.02 (p=0.002) in the moderate-risk group and 3.41 (p<0.001) in the high-risk group; for OS, HRs were 3.05 (p=0.001) and 5.63 (p<0.001), respectively. OCCI, Eastern Cooperative Oncology Group (ECOG) status, and the International Federation of Gynecology and Obstetrics (FIGO) stage were independent predictors of PFS. In contrast, OCCI, FIGO stage, and cytoreductive surgery were independent predictors of OS. Conclusion: OCCI is a valuable tool for predicting survival and informing clinical decision-making in patients with EOC. The burden of comorbidities can significantly influence treatment choices and survival, particularly in elderly and advanced-stage patients. Incorporating OCCI into clinical practice may support the development of personalized and multidisciplinary treatment strategies, ultimately enhancing treatment outcomes.